The impact of level of debt of companies toward its profitability: evidence from Malaysia / Elmy Fionaricka Victor - Victor, Elmy Fionaricka (2017)
This paper is studying about the relationship between high and low debt toward the companies’ profitability if companies listed in Bursa Malaysia Derivatives Bhd. by running a data using stata12. 100 random companies that have been listed in Bursa Malaysia are selected by latest 8 years data. The studies are using debt to equity ratio, total debt and long – term debt to asset ratio as independent variables and return on asset as dependent variables to identify the relationship between debt and profit. From the result it reveals that the high level of debt contribute to high profit but debt must be in right portion and should be controlled to avoid an excess debt as there is negative and positive relationship between debt and profitability of a companies.